Probabilistic dynamic amplification of Australian B-Double trucks - ICASP14; Cantero, Daniel; Caprani, Colin; Mei, Shiyi (My University, 2023)
Traffic loading is one of the most common and important live loads to which bridges are subjected. In particular, the dynamic effect caused by running vehicles plays an important role in determining the structural safety of bridges subjected to traffic loading. The Dynamic Amplification Factor (DAF) is widely used to determine dynamic stresses in bridges. Many researchers have modeled the actions of rigid vehicles or semi-trailers by Vehicle-Bridge-Interaction (VBI) simulations. However, far less research has focused on the probabilistic analysis of typical 9-axle B-Double heavy vehicles which feature a tractor and two trailers. For these vehicles, this work develops the relationship between the DAF, static bending moment at mid-span bridge, and Gross Vehicle Mass (GVM) through Monte Carlo (MC) simulation with a set of observed B-Double parametric data. The outcome of this study provides a quick and simple way to predict the interaction between 9-axle B-Double vehicles and common types of simply supported bridges in Australia under different classes of road profile conditions.
14th International Conference on Applications of Statistics and Probability in Civil Engineering(ICASP14)
PUBLISHED